A Review on Newer Ocular Drug Delivery Systems with an Emphasis on Glaucoma - Maneesha Peter (Tabriz University of Medical Sciences, 2020)
Glaucoma is an irreversible condition resulting from the increase in intraocular pressure (IOP); which leads to permanent loss of vision with the destruction of retinal ganglion cells (RGCs). The IOP elevations are controlled in normal by the physiological flow of aqueous humour. A population with age above 40 is more susceptible to glaucoma. Other factors like gender, genetics, race etc. plays major roles in the development of the disease. Current treatment methods available for the disease includes drugs come under the classes of beta receptor blockers, carbonic anhydrase inhibitors, cholinergic agonists, prostaglandins etc. N-methyl-D-aspartate (NMDA) antagonists, inducible nitric oxide synthase (iNOS) inhibition, cytoskeletal agents, Rho-kinase inhibitors etc are few novel targets sites which are in research focus for the treatment of the disease. Developments in nanomedicine are also being evaluated for their potential in treating the growing glaucomatous population. Nanosystems are suggested to avoid the difficulties in tackling the various ocular barriers to a limit, help to decrease the instillation frequency of topical medication and can provide drug delivery in a sustained or controlled manner. This review focuses on the current and emerging treatment methods for glaucoma along with some of the nanoformulations for ocular drug delivery.